Faith like potatoes - Buchan, Angus; Van den Bergh, Regardt; d; Rautenbach, Frank, 1972-; Dhlamini, Hamilton; Wilhelm, Jeanne; McLachlan, Grant; Buchan, Angus; Affirms Films (Firm); Global Creative Studios; Carmel Entertainment Group; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
A farmer moves his family to South Africa and suffers a series of seemingly insurmountable losses. Through unlikely friendships and much needed divine intervention, he discovers his life's true purpose and it sustains his unwavering belief in the power of faith.
DVD, anamorphic widescreen (1.85:1) presentation; Dolby Digital 5.1.
In English with optional English, French, and Spanish subtitles; closed-captioned.
Frank Rautenbach, Hamilton Dhlamini, Jeanne Wilhelm.
Music, Grant McLachlan ; editor, Ronelle Loots ; director of photography, Dave Aenmey ; costume designer, Claudia Littlefield.
Based on the book "Faith Like Potatoes" by Angus Buchan.
Originally produced as a motion picture in 2006.
Keywords: Buchan, Angus -- Drama; Farmers -- South Africa -- Drama; Families -- Drama; Faith -- Drama; Video recordings for hard of hearing people; Biographical films; Feature films; Fiction films; Biographical films